HPV Infections in Heterosexual Couples: Mechanisms and Covariates of Virus Transmission - Kero K.; Rautava J. (KARGER, 2022)
Sexual intercourse is regarded as the primary route of human papillomavirus (HPV) transmission. Reported rates of the genotype-specific genital concordance of HPV infection among heterosexual partners vary. Most studies have evaluated only male/female genital transmission, but lately, the oral region has gained interest because of a rising trend of HPV-associated oropharyngeal cancer. Risk factors for type-specific concordance have been reported as an increasing number of younger couples, persistent HPV infection, higher frequency of sexual intercourse, rising number of spouse's lifetime sexual partners, and sexual relations with prostitutes. However, the concordance of the same genital HPV genotype does not absolutely mean that it has been transmitted by the current partner. There are also other possible non-sexual transmission routes. The detected HPV infection may also be a reactivation of a previous infection. The high complexity of HPV transmission dynamics within an individual him-/herself as well as within sexual couples is discussed in this article.